PROVENANCE IMPLICATIONS OF TH-U-PB ELECTRON MICROPROBE AGES FROM DETRITAL MONAZITE IN THE CARBONIFEROUS UPPER SILESIA COAL BASIN, POLAND - Kusiak M.A.; Kedzior A.; Paszkowski M.; Doktor M.; Suzuki K.; González-Álvarez I.; Wajsprych B. (My University, 2006)
This paper reports the results of CHIME (chemical Th-U-Pb isochron method) dating of detrital monazites from Carboniferous sandstones in the Upper Silesia Coal Basin (USCB). A total of 4739 spots on 863 monazite grains were analyzed from samples of sandstone derived from six stratigraphic units in the sedimentary sequence. Age distributions were identified in detrital monazites from the USCB sequence and correlated with specific dated domains in potential source areas. Most monazites in all samples yielded ca. 300-320 Ma (Variscan) ages; however, eo-Variscan, Caledonian and Cadomian ages were also obtained. The predominant ages are comparable to reported ages of certain tectonostratigraphic domains in the polyorogenic Bohemian Massif (BM), which suggests that various crystalline lithologies in the BM were the dominant sources of USCB sediments. © 2005 Elsevier B.V. All rights reserved.
Keywords: BOHEMIAN MASSIF; ELECTRON MICROPROBE DATING; GEOCHRONOLOGY; MONAZITE; PROVENANCE; UPPER SILESIA COAL BASIN; Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная